2016
DOI: 10.1515/revac-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the analysis of polybrominated diphenyl ethers and polybrominated biphenyls in plastic

Abstract: Polybrominated diphenyl ethers (PBDEs) and polybrominated biphenyls (PBBs), heavily used as flame retardant in plastics, are harmful to environment and human health. It is of great importance for method development to determine PBDEs and PBBs in plastics. A review of developments on the analysis of PBDEs and PBBs in plastics is presented in this paper. The analytical procedures including sample pretreatment, extraction, clean-up/fractionation, and detection are carefully discussed. The drawbacks and merits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Supercritical CO 2 is often used as an extracting solvent, which has the capability of attaining recoveries above 97%. Moreover, the extraction efficiency of SFE can be further improved by the use of modifiers such as acetonitrile, toluene, and tetrahydrofuran [89]. A successful application of SFE in the extraction of PBDEs from polymeric materials was reported by Peng et al [90].…”
Section: Sample Pre-treatment Methodsmentioning
confidence: 99%
“…Supercritical CO 2 is often used as an extracting solvent, which has the capability of attaining recoveries above 97%. Moreover, the extraction efficiency of SFE can be further improved by the use of modifiers such as acetonitrile, toluene, and tetrahydrofuran [89]. A successful application of SFE in the extraction of PBDEs from polymeric materials was reported by Peng et al [90].…”
Section: Sample Pre-treatment Methodsmentioning
confidence: 99%
“…PBDEs and polybrominated biphenyl [PBBs] as flame retardants in plastic ( 50 ) can decrease the circulating level of thyroid hormones and are associated with impaired thyroid function ( 51 ). It has been reported that five weeks of rats’ exposure to 1, 3, 6, and 10mg/kg/day of polystyrene nanoplastics [PS-NPs] suppress the serum level of T3, FT3, and FT4 synthesis and circulating level of thyroid hormones ( 41 ) ( Table 2 ).…”
Section: Effects Of Mps Nps and Associated Chemicals On The Mammalian...mentioning
confidence: 99%